Heritage Preservation, Conservation and/or Restoration: Old Government Buildings in the 1990s - Falconer, Tamsin (Architectural History Aotearoa, 2020)
In the 1990s, a $25 million project under the management of the Department of Conservation restored the "largest wooden office building in the Southern Hemisphere," converting it into the home of the Victoria University of Wellington School of Law. The restoration project took roughly the same length of time as the original construction. This paper will present the 1990s work on Old Government Buildings as a case study of heritage practice in the 1990s. We will discuss aspects such as the retention of the heritage lift, the reinstatement of "chimneys" using 1990s construction techniques, use of native timbers, and the decisions made on replication, restoration and strengthening that may or may not be made differently today.